2015
DOI: 10.1186/s12348-015-0062-z
|View full text |Cite
|
Sign up to set email alerts
|

Uveitic band keratopathy: child and adult

Abstract: BackgroundCalcified band keratopathy is a chronic degenerative disease characterized by the deposition of gray to white opacity in superficial layers of the cornea that typically develops over months or years. It is associated with a variety of conditions, including chronic uveitis.PurposeThe objective of this study is to assess visual acuity and corneal changes in patients with band keratopathy secondary to uveitis who underwent phototherapeutic keratectomy (PTK).SettingThe place where this study was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 7 publications
0
10
1
2
Order By: Relevance
“…In the current study, the IRR of keratopathies in patients diagnosed with uveitis is higher than that in the control group with a significantly greater aHR and cumulative probability. Except for the development of band keratopathies in uveitic patients reported previously, 20 the current study showed a universal risk of developing keratopathies in the whole uveitis population by excluding the occurrence of band keratopathies. Moreover, the previous studies mainly focused on the correlation between the anterior uveitis and corneal disorders, [14][15][16] whereas panuveitis yielded a significant effect on the development of keratopathies in the current study.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…In the current study, the IRR of keratopathies in patients diagnosed with uveitis is higher than that in the control group with a significantly greater aHR and cumulative probability. Except for the development of band keratopathies in uveitic patients reported previously, 20 the current study showed a universal risk of developing keratopathies in the whole uveitis population by excluding the occurrence of band keratopathies. Moreover, the previous studies mainly focused on the correlation between the anterior uveitis and corneal disorders, [14][15][16] whereas panuveitis yielded a significant effect on the development of keratopathies in the current study.…”
Section: Discussioncontrasting
confidence: 49%
“…The previous studies showed that uveitis, especially chronic uveitis, would lead to band keratopathy. 20,21 Nevertheless, the inflammatory process in uveitis that involves cytokine alteration such as IL-6 and TNF may influence the corneal condition, 17 because the use of cyclosporine that suppresses interleukin activity can relieve some categories of keratopathies. 22 Moreover, the corneal endothelial cells were damaged with an altered central corneal thickness in patients with uveitis, [14][15][16]23 whereas inflammatory cell infiltration into the corneal stoma was also observed during the onset of anterior uveitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this cohort study, we evaluated these comorbidities in ESRD patients and controls and found that iridocyclitis and phthisis bulbi are associated with higher incidences of band keratopathy in the ESRD patients compared with that in the controls ( Table 2 ) and are significant risk factors for band keratopathy in the cohort ( Table 3 ). Many reports demonstrated the link between iridocyclitis and band keratopathy 11 27 28 . They suggested that although the exact mechanism of calcium-phosphate precipitation in the superficial layers of cornea is unknown, it may result from deposition left as degeneration and necrosis from chronic inflammation related to iridocyclitis 11 27 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Many reports demonstrated the link between iridocyclitis and band keratopathy 11 27 28 . They suggested that although the exact mechanism of calcium-phosphate precipitation in the superficial layers of cornea is unknown, it may result from deposition left as degeneration and necrosis from chronic inflammation related to iridocyclitis 11 27 28 . ESRD patients with iridocyclitis should be advised to control their inflammation through regular follow-up and treatment by ophthalmologists because of significant association with subsequent band keratopathy.…”
Section: Discussionmentioning
confidence: 99%